Tools for teaching in an educationally mobile world - Carroll, Jude (Internationalization in higher education series, 2015)
"Tools for Teaching in an Educationally Mobile World examines the challenges that undergraduate and postgraduate teachers often encounter when working with students from different national and cultural backgrounds. It focuses on the consequences for interactive teaching and for course design in a world where students, ideas and courses are mobile, using examples and experiences from a wide range of disciplines and national contexts. It not only considers Anglophone countries, including the USA, Canada, the UK, Australia and New Zealand, but also the use of English as a language of instruction in countries where neither teachers nor students are native English speakers"--